PENDIDIKAN KESEHATAN REPRODUKSI REMAJA DI SMPN 52 SURABAYA - Hanifa Fitriana; Pulung Siswantara (Universitas Airlangga, 2018)
Teenager is a period of rapid physical, psychological and intellectual development. Adolescents tend to like challenges without careful consideration. This caused various problems of adolescents, especially in reproductive health. Adolescent Reproductive Health (ARH) Education by teachers is an effort to overcome the problem of reproductive health of students. The purpose of this research was to identify the transfer process of adolescent reproductive health education at SMPN 52 Surabaya. This research used observational case study research with qualitative approach. Informants in this study consisted of teachers and students. Data was collected through in-depth interviews and document studies. This study found that most teacher informants have poor understanding of comprehensive ARH. The teacher informants said that ARH education is the responsibility of parents, school, community and government. The teacher informants delivered the ARH material with various methods. Teacher separated male and female students during delivering process of sensitive ARH materials. This method can encourage students' activeness to ask questions to the teachers. A better understanding of teachers on KRR materials can improve the quality of students' material delivery.ARH education is not only the responsibility of the school, but also family, community to government. The government needs to provide training for teachers related to theARH education. Families need to provide ARH education at home, meanwhile the community needs to provide supervision for adolescents in their neighborhood.